ASUHAN KEPERAWATAN PADA An. Z DENGAN DENTAL CALCULUS (KARANG GIGI) DI WILAYAH RT 004/ RW 007 KELURAHAN LIMO KOTA DEPOK - Cut Annisa Qistina Nubli (2023)
Background : Dental and oral health is often ignored, especially by parents to their children so that diseases arise in children's dental and oral health. One of the diseases in dental and oral health in children that may arise is periodontal disease, where the disease starts from the presence of plaque or accumulation of food residue that sticks to the surface of the teeth. Plaque that is left in place for a long time can cause calculus. Calculus or tartar is a collection of plaque that has deposited and then sticks to the teeth which makes the teeth rough and feel thick. The mode of tartar formation for each human being is different and varies greatly. Tartar is referred to as a factor of gradual and continuous interference with the gums and causes inflammation of the gums. Treatment of tartar can be done independently at home with oral hygiene measures. Purpose : Writing scientific papers aims to find out how to apply nursing care for children with tartar. Method : The method of writing this scientific paper uses case studies which were carried out from February to March 2023. And by using data collection obtained using interviews, observation, and documentation. Results : There were 4 pieces of tartar on An.Z and oral hygiene education had been carried out. Conclusion : The implementation of the nursing care provided is appropriate, so that the diagnoses that arise can be resolved. Keywords : Tartar, Plaque, Calculus